High-performance magnesium-based composite hydrogen storage material as well as preparation method and application thereof
By reacting Mo2V2AlC3 powder with HF solution to form a Mo2V2C3 MXene catalyst and ball milling with MgH2 powder, MgH2-x wt%Mo2V2C3 magnesium-based composite hydrogen storage material was prepared, which solved the problems of high hydrogen absorption/discharge temperature, slow kinetic performance and poor cycle stability in the MgH2 hydrogen storage material during hydrogen storage, and achieved lower hydrogen absorption/discharge temperature, faster kinetic performance and excellent cycle stability.
Patent Information
- Application Number
- CN202411968301.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing MgH2 hydrogen storage materials have problems such as high hydrogen absorption/discharge temperature, slow kinetic performance and poor cycle stability during hydrogen storage, which limits their large-scale application.
The Mo2V2AlC3 MXene catalyst was formed by reacting Mo2V2C3 powder with HF solution and ball milling with MgH2 powder to prepare MgH2-x wt% Mo2V2C3 magnesium-based composite hydrogen storage material. This method improves the catalytic activity and mixing uniformity of the material through weak acid etching and ball milling.
It realizes lower hydrogen absorption/discharge temperature, faster dynamic performance and excellent cycle stability of MgH2-x wt%Mo2V2C3 composite hydrogen storage material, and is suitable for hydrogen energy vehicles and energy storage systems.
Smart Images

Figure CN119873741A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials and relates to a high-performance magnesium-based composite hydrogen storage material and a preparation method and application thereof. Background Art
[0002] In recent years, with the gradual depletion of fossil energy, environmental and climate problems have become increasingly severe. Reducing dependence on traditional fossil energy and developing clean, efficient and sustainable alternative energy sources have become urgent needs and common goals for countries around the world. Hydrogen energy is considered to be one of the most promising clean energy carriers due to its high calorific value and the fact that both its raw materials and products are water. It is expected to become the most ideal alternative energy source. The development of hydrogen energy includes three links: hydrogen production, hydrogen storage, and hydrogen use. As a key bridge connecting the hydrogen production and application ends, hydrogen storage technology is facing many challenges such as low safety and low energy density. Compared with other hydrogen storage methods, solid-state hydrogen storage has the advantages of safety, reliability, and high energy density. Its technological development has become a research hotspot in the field of hydrogen storage.
[0003] Among many hydrogen storage materials, MgH2 has become the focus of researchers' development and optimization due to its high hydrogen storage density (7.6wt%), good cycle performance and abundant natural reserves. However, problems such as easy agglomeration, high thermodynamic stability and slow kinetics in the hydrogen storage process restrict its large-scale application. At present, people mainly modify MgH2 through nano-sizing, alloying, adding catalysts and other methods, and have made significant breakthroughs in room temperature hydrogen absorption, rapid hydrogen release, and improved cycle performance. However, there is still a long way to go before MgH2 hydrogen storage can be put into practical use on a large scale.
[0004] A large number of studies have shown that two-dimensional MXene is a highly catalytically active material with a special accordion shape, stable structure, and good conductivity. Its special layered structure and properties can effectively prevent MgH2 from agglomerating, reduce the temperature of MgH2 hydrogen absorption / desorption, accelerate its hydrogen absorption / desorption rate, and optimize its cyclic hydrogen absorption / desorption performance. Among them, double transition metal MXene materials can also provide more active sites and channels for electron and hydrogen transfer, and can be used as a good catalyst to improve the comprehensive hydrogen storage performance of MgH2, which is of great significance for realizing long-term and efficient hydrogen storage of MgH2 in practical applications, such as in hydrogen energy vehicles and energy storage systems.
[0005] Chinese patent application CN202111077460.0 discloses a method for preparing a high-performance and high-capacity Mg-Al-Y based hydrogen storage material, which comprises heating and melting the raw materials in a medium-frequency induction melting furnace under an inert atmosphere, casting and molding, pulverizing the ingot into powders of 200-300 mesh, mixing the porous carbon-based catalyst Tm@C loaded with transition metals and metal fluorides for high-energy ball milling, and obtaining a hydrogen storage material composed of the following components: Mg x Aly Y z +a%Tm@C+b%metal fluoride, including:Mg x Al y Y z It is a Mg-Al-Y hydrogen storage alloy, x, y, z are atomic ratios, where x+y+z=100, 5≤y≤15, 5≤z≤10, a, b are the mass percentages of Tm@C and metal fluoride added based on the mass of Mg-Al-Y hydrogen storage alloy powder, and a, b are 3 to 5. However, the hydrogen storage material provided by the patent has the defects of low hydrogen storage capacity, high hydrogen desorption temperature, slow hydrogen absorption / desorption kinetics, etc. Summary of the invention
[0006] The purpose of the present invention is to provide a high-performance magnesium-based composite hydrogen storage material and a preparation method and application thereof, which has a lower hydrogen absorption / desorption temperature, faster kinetic performance and excellent cycle stability.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a high-performance magnesium-based composite hydrogen storage material, comprising the following steps:
[0009] S1. Place the HF solution in a container with a cover, heat it to the target temperature and keep it warm for later use;
[0010] S2, adding the precursor Mo2V2AlC3 powder to the HF solution in S1, and reacting at the target temperature, centrifuging, washing, and filtering the obtained reaction product, and freeze-drying the obtained precipitate to obtain Mo2V2C3MXene powder;
[0011] S3. Mix the Mo2V2C3 MXene powder and the MgH2 powder in a mass ratio of x:100-x, transfer the mixture to a ball mill for ball milling, and obtain the desired MgH2-x wt% Mo2V2C3 magnesium-based composite hydrogen storage material, wherein the value of x ranges from 5 to 40, and illustratively can be 5, 7.5, 10, 12.5, 40, etc.
[0012] Furthermore, the mass fraction of the HF solution is 40-60%, preferably 50%.
[0013] Furthermore, the target temperature is 50-60°C, preferably 55°C.
[0014] Furthermore, the ratio of the added amount of the precursor Mo2V2AlC3 powder to the HF solution is (0.8-1.2) g:20 mL, preferably 1 g:20 mL.
[0015] Furthermore, in S2, the reaction time is 72 to 144 hours, preferably 96 hours.
[0016] Furthermore, in S2, the washing process is: washing the centrifuged product with deionized water until the supernatant is neutral.
[0017] Furthermore, in S2, the freeze-drying temperature is below -35°C, and the time is 12 to 36 hours, preferably 24 hours.
[0018] Furthermore, in S3, during the ball milling treatment, the ball-to-material ratio is controlled to be 55-65:1, preferably 60:1, the ball milling speed is 400-600 rpm, preferably 500 rpm, and the time is 8-12 h, preferably 10 h.
[0019] In a second aspect, the present invention provides a high-performance magnesium-based composite hydrogen storage material, which is prepared by the preparation method as described above. The composition of the composite hydrogen storage material is MgH2-x wt% Mo2V2C3, and its main phase is MgH2 powder. Mo2V2C3 is a new two-dimensional MXene material with an obvious accordion-like structure obtained by hydrofluoric acid etching. The main phase MgH2 powder and Mo2V2C3 powder are evenly mixed by ball milling.
[0020] In a third aspect, the present invention provides an application of a high-performance magnesium-based composite hydrogen storage material in hydrogen energy vehicles and energy storage systems.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The prepared high-performance MgH2-x wt% Mo2V2C3 (x=5, 7.5, 10, 12.5, 40) magnesium-based composite hydrogen storage material has a lower hydrogen absorption / desorption temperature, faster kinetic performance and excellent cycle stability.
[0023] (2) Using conventional samples such as MgH2 powder, HF, and precursor Mo2V2AlC3 powder as raw materials, it is prepared based on weak acid etching and ball milling. The etching product of Mo2V2C3 MXene material has high purity, the preparation method is simple, MgH2-x wt% Mo2V2C3 (x = 5, 7.5, 10, 12.5, 40) hydrogen storage material has excellent performance, the addition amount of Mo2V2C3MXene material is small, the hydrogen storage process is not easy to agglomerate, the cost is low, and it can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an image of the catalyst Mo2V2C3 MXene powder prepared in Example 1, wherein: Figure 1 (a) is the TEM spectrum, Figure 1 (b) is the SEM image; Figure 1 (c) is the selected area electron diffraction pattern.
[0025] Figure 2 This is an image of the MgH2+10wt%Mo2V2C3 composite material prepared in Example 1. Figure 2 (a) is the SEM image of the MgH2+10wt%Mo2V2C3 composite material after ball milling. Figure 2 (b) is the SEM image of the MgH2+10wt% Mo2V2C3 composite material after dehydrogenation, and (c) is the SEM image of the MgH2+10wt% Mo2V2C3 composite material after re-absorption of hydrogen.
[0026] Figure 3 The temperature-programmed desorption (TPD) curves of the MgH2+10wt% Mo2V2C3 composite hydrogen storage material prepared in Example 1 and the corresponding control sample.
[0027] Figure 4 This is the programmed temperature adsorption (TPA) curve of the MgH2+10wt% Mo2V2C3 composite hydrogen storage material prepared in Example 1 and the corresponding control sample.
[0028] Figure 5 Isothermal hydrogen desorption curves of the MgH2+10wt% Mo2V2C3 composite hydrogen storage material prepared in Example 1 at 275°C, 300°C, 325°C, and 350°C.
[0029] Figure 6 This is the activation energy curve of the hydrogen desorption reaction of the MgH2+10wt% Mo2V2C3 composite material prepared in Example 1 at 275℃, 300℃, 325℃, and 350℃.
[0030] Figure 7 XRD spectra of the Mo2V2C3 MXene catalyst and MgH2+10wt% Mo2V2C3 composite material prepared in Example 1 after ball milling, dehydrogenation, and re-hydrogenation.
[0031] Figure 8 This is the HRTEM image of the MgH2+40wt% Mo2V2C3 composite material prepared in Example 5 after hydrogen absorption. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0033] In the following examples, the Mo2V2AlC3 powder used was purchased from Xinxin Technology Co., Ltd.; magnesium hydride powder (MgH2, purity 99.9%) and hydrofluoric acid (HF, concentration 50%) are both conventional commercial products in the field.
[0034] Example 1
[0035] The preparation method of the high-performance MgH2+10wt%Mo2V2C3 magnesium-based composite hydrogen storage material of the present invention comprises the following specific steps:
[0036] (1) Take 20 ml of 50% HF solution and place it in a polytetrafluoroethylene liner with a lid, transfer it to an oil bath filled with silicone oil, heat it to 55°C and keep it at a constant temperature for later use;
[0037] (2) Add 1 g of precursor Mo2V2AlC3 powder into the above HF solution in small amounts and multiple times (generally about four to five times), and keep the reaction at 55°C for 96 hours for later use.
[0038] (3) The sample obtained in step (2) is centrifuged and washed with deionized water for multiple times until the supernatant is neutral, and then set aside.
[0039] (4) Filter the sample obtained in step (3) to remove excess water, and retain the precipitate for later use.
[0040] (5) The precipitate obtained in step (4) is freeze-dried for 24 hours to obtain a dry Mo2V2C3MXene catalyst powder, and the catalyst is recovered for later use.
[0041] Figure 1 Figures (a), (b) and (c) respectively show the TEM image (a), SEM (b) image and selected area electron diffraction (c) of the Mo2V2C3 MXene catalyst prepared in this step. As shown in the figure, the Mo2V2C3 MXene catalyst has an obvious accordion-like structure, and the thickness of each single layer is less than 1nm. This accordion-like structure has good stability, which is not only conducive to preventing the agglomeration of MgH2, but also provides more channels for hydrogen transmission in the Mg / MgH2 absorption / desorption process.
[0042] (6) Weigh 450 mg of MgH2 powder and 50 mg of the Mo2V2C3 MXene catalyst obtained in step (5) and place them in a 100 ml ball milling jar, control the ball-to-material ratio to 60:1, and ball mill for 10 h at a speed of 500 rpm. The desired high-performance MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material is obtained.
[0043] Figure 2Figures (a), (b) and (c) respectively show the SEM images of the high-performance MgH2-10wt% Mo2V2C3 magnesium-based composite hydrogen storage material obtained in this step after ball milling, after dehydrogenation, and after hydrogen reabsorption. Figure 2 It can be seen that the MgH2 powder and Mo2V2C3 powder are evenly mixed after ball milling, and the particles are small and the particles are loosely stacked without obvious agglomeration. After dehydrogenation, the particle size of the composite hydrogen storage material becomes larger and slight agglomeration occurs. After absorbing hydrogen again, its particle size is still small and the agglomeration phenomenon is not aggravated. This shows that the relatively stable accordion-like structure of the catalyst Mo2V2C3 MXene powder effectively inhibits the agglomeration of Mg / MgH2 in the hydrogen absorption / desorption process.
[0044] Figure 4 The temperature-programmed adsorption (TPA) curves of the high-performance MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material prepared in this step and the comparative sample are given in FIG. Figure 3 As shown in the figure, the MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material can quickly absorb hydrogen from room temperature and reach a hydrogen absorption saturation state when the temperature rises to 200°C. This shows that the introduction of Mo2V2C3 MXene makes the MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material have excellent hydrogen absorption performance.
[0045] Figure 5 The dehydrogenation curves of the high-performance MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material prepared in this step at 275°C, 300°C, 325°C, and 350°C are given in FIG. Figure 5 As shown in the figure, at 300°C, the MgH2-10wt% Mo2V2C3 composite hydrogen storage material can completely release hydrogen within 30 minutes. This shows that the introduction of Mo2V2C3 MXene is beneficial to accelerate the dehydrogenation kinetics of MgH2.
[0046] Figure 6 The JMA fitting activation energy of the high-performance MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material prepared in this step is given as follows: Figure 5 As shown in Figure 2, the activation energy of MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material is as low as 87.7 kJ / mol -1 This indicates that the introduction of Mo2V2C3 MXene is beneficial to the hydrogen desorption reaction of MgH2.
[0047] Figure 7 The XRD images of the high-performance MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material prepared in this step after ball milling, dehydrogenation, and re-hydrogenation are given. Figure 7It can be seen that the composite hydrogen storage materials after ball milling, dehydrogenation, and re-absorption of hydrogen all contain Mo2V2C3 peaks, and no other new phases are generated except Mg and MgH2, indicating that Mo2V2C3 MXene mainly plays a catalytic role as a catalyst in the MgH2-10 wt% Mo2V2C3 magnesium-based composite hydrogen storage material.
[0048] Example 2
[0049] (1) Take 20 ml of 50% HF solution and place it in a polytetrafluoroethylene liner with a lid, transfer it to an oil bath filled with silicone oil, heat it to 55°C and keep it at a constant temperature for later use;
[0050] (2) Add 1 g of precursor Mo2V2AlC3 powder into the above HF solution in small amounts and keep the reaction at 55°C for 96 hours to obtain a mixture for later use.
[0051] (3) The sample obtained in step (2) is centrifuged and washed with deionized water for multiple times until the supernatant is neutral, and then set aside.
[0052] (4) Filter the sample obtained in step (3) to remove excess water, and retain the precipitate for later use.
[0053] (5) The precipitate obtained in step (4) is freeze-dried for 24 hours to obtain a dry Mo2V2C3MXene catalyst powder, and the catalyst is recovered for later use.
[0054] (6) 475 mg of MgH2 powder and 25 mg of the Mo2V2C3 catalyst obtained in step (5) were placed in a 100 ml ball mill, the ball-to-material ratio was controlled to be 60:1, and the ball milling was performed at a speed of 500 rpm for 10 h. The desired MgH2-5wt% Mo2V2C3 composite hydrogen storage material was obtained.
[0055] Example 3
[0056] (1) Take 20 ml of 50% HF solution and place it in a polytetrafluoroethylene liner with a lid, transfer it to an oil bath filled with silicone oil, heat it to 55°C and keep it at a constant temperature for later use;
[0057] (2) Add 1 g of precursor Mo2V2AlC3 powder into the above HF solution in small amounts and keep the reaction at 55°C for 96 hours to obtain a mixture for later use.
[0058] (3) The sample obtained in step (2) is centrifuged and washed with deionized water for multiple times until the supernatant is neutral, and then set aside.
[0059] (4) Filter the sample obtained in step (3) to remove excess water, and retain the precipitate for later use.
[0060] (5) The precipitate obtained in step (4) is freeze-dried for 24 hours to obtain a dry Mo2V2C3MXene catalyst powder, and the catalyst is recovered for later use.
[0061] (6) 462.5 mg of MgH2 powder and 37.5 mg of the Mo2V2C3 MXene catalyst obtained in step (5) were placed in a 100 ml ball milling jar with a ball-to-material ratio of 60:1, and ball milled at a speed of 500 rpm for 10 h. The desired MgH2-7.5 wt% Mo2V2C3 composite hydrogen storage material was obtained.
[0062] Example 4
[0063] (1) Take 20 ml of 50% HF solution and place it in a polytetrafluoroethylene liner with a lid, transfer it to an oil bath filled with silicone oil, heat it to 55°C and keep it at a constant temperature for later use;
[0064] (2) Add 1 g of precursor Mo2V2AlC3 powder into the above HF solution in small amounts and keep the reaction at 55°C for 96 hours to obtain a mixture for later use.
[0065] (3) The sample obtained in step (2) is centrifuged and washed with deionized water for multiple times until the supernatant is neutral, and then set aside.
[0066] (4) Filter the sample obtained in step (3) to remove excess water, and retain the precipitate for later use.
[0067] (5) The precipitate obtained in step (4) is freeze-dried for 24 hours to obtain a dry Mo2V2C3MXene catalyst powder, and the catalyst is recovered for later use.
[0068] (6) 437.5 mg of MgH2 powder and 62.5 mg of the Mo2V2C3 MXene catalyst obtained in step (5) were placed in a 100 ml ball mill with a ball-to-material ratio of 60:1, and ball milled at 500 rpm for 10 h. The desired MgH2-12.5 wt% Mo2V2C3 composite hydrogen storage material was obtained.
[0069] Attached Figure 3 The temperature programmed desorption (TPD) curves of the MgH2-x wt% Mo2V2C3 composite hydrogen storage material prepared in Examples 2-4 and the comparative sample are shown in FIG. Figure 3As shown in the figure, with the increase of the addition ratio of Mo2V2C3 MXene, the initial dehydrogenation temperature of the MgH2-x wt%Mo2V2C3 composite hydrogen storage material gradually decreases, among which the initial dehydrogenation temperature of the MgH2-10 wt%Mo2V2C3 composite hydrogen storage material decreases to 180°C, the peak dehydrogenation temperature is 260°C, and the dehydrogenation is complete at 300°C, with a dehydrogenation amount of up to 6.6wt%. In contrast, the initial dehydrogenation temperature of the MgH2-x wt%Mo2V2C3 (x=5,7.5) composite hydrogen storage material is slightly higher, while the dehydrogenation amount of the MgH2-12.5wt%Mo2V2C3 composite hydrogen storage material is slightly lower. This shows that the MgH2-10 wt%Mo2V2C3 composite hydrogen storage material has better comprehensive hydrogen storage performance.
[0070] Example 5
[0071] (1) Take 20 ml of 50% HF solution and place it in a polytetrafluoroethylene liner with a lid, transfer it to an oil bath filled with silicone oil, heat it to 55°C and keep it at a constant temperature for later use;
[0072] (2) Add 1 g of precursor Mo2V2AlC3 powder into the above HF solution in small amounts and keep the reaction at 55°C for 96 hours to obtain a mixture for later use.
[0073] (3) The mixture after the reaction in step (2) is centrifuged and washed with deionized water for multiple times until the solution is neutral, and then set aside.
[0074] (4) The mixed solution obtained in step (3) is filtered to remove excess water, and the precipitate is retained for later use.
[0075] (5) The precipitate obtained in step (4) is freeze-dried for 24 hours to obtain a dry Mo2V2C3MXene catalyst powder, and the catalyst is recovered for later use.
[0076] (6) 300 mg of MgH2 powder and 200 mg of the Mo2V2C3 MXene catalyst obtained in step (5) were placed in a 100 ml ball milling jar with a ball-to-material ratio of 60:1, and ball milled at a speed of 500 rpm for 10 h. The desired MgH2-40 wt% Mo2V2C3 composite hydrogen storage material was obtained.
[0077] Attached Figure 8 The HRTEM image of the MgH2-40 wt% Mo2V2C3 composite hydrogen storage material prepared in this step after hydrogen absorption is given in FIG. Figure 8As shown in the figure, the stripes with lattice spacing d = 0.154nm and d = 0.213nm correspond to Mo2V2C3 MXene catalysts, and the stripes with d = 0.149nm, d = 0.250nm and d = 0.251nm correspond to MgH2 materials. After the composite hydrogen storage material absorbs hydrogen again, Mo2V2C3 MXene still exists, and no other new phases are produced, which once again shows that Mo2V2C3 MXene plays a catalytic role in MgH2-40 wt% Mo2V2C3 as a catalyst. In addition, the HRTEM image after hydrogen absorption shows that the crystal planes of Mo2V2C3 MXene and MgH2 always appear alternately, forming many two-phase interfaces, which provide a large number of hydrogen transmission channels for the Mg / MgH2 absorption / desorption process.
[0078] Comparative Example
[0079] 450 mg of MgH2 powder and 50 mg of precursor Mo2V2AlC3 powder were placed in a 100 ml ball milling jar, the ball-to-material ratio was controlled to be 60:1, and the ball milling was performed at a speed of 500 rpm for 10 hours to obtain a comparative sample MgH2-10 wt% Mo2V2AlC3 composite hydrogen storage material.
[0080] Attached Figure 3 and 4 The results of (Temperature Programmed Desorption) TPD and (Temperature Programmed Adsorption) TPA performance tests of MgH2-10 wt% Mo2V2C3 composite material and MgH2-10 wt% Mo2V2AlC3 composite material are provided in the literature, wherein the initial dehydrogenation temperatures of MgH2-10 wt% Mo2V2C3 composite material and MgH2-10 wt% Mo2V2AlC3 comparative sample are 180°C and 190°C, respectively, and both can absorb hydrogen from room temperature, but the hydrogen absorption rate and amount of MgH2-10wt% Mo2V2C3 composite material are significantly higher than those of MgH2-10 wt% Mo2V2AlC3 comparative sample. It can be seen that the performance of MgH2-10 wt% Mo2V2C3 composite material in terms of dehydrogenation thermodynamics, hydrogen absorption kinetics and hydrogen storage capacity is better than that of MgH2-10 wt% Mo2V2AlC3 comparative sample.
[0081] The above description of the embodiments is to facilitate those skilled in the art to understand and use the invention.
[0082] These embodiments are modified in various ways, and the general principles described herein are applied to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance magnesium-based composite hydrogen storage material, characterized in that: The following steps are involved: S1. Place the HF solution in a container with a cover, heat it to the target temperature and keep it warm for later use; S2, adding the precursor Mo2V2AlC3 powder to the HF solution in S1, and reacting at the target temperature, centrifuging, washing, and filtering the obtained reaction product, and freeze-drying the obtained precipitate to obtain Mo2V2C3MXene powder; S3. Mix the Mo2V2C3 MXene powder and the MgH2 powder in a mass ratio of x:100-x, transfer the mixture to a ball mill for ball milling, and obtain the desired MgH2-x wt% Mo2V2C3 magnesium-based composite hydrogen storage material, wherein the value of x ranges from 5 to 40.
2. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: The mass fraction of the HF solution is 40-60%.
3. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: The target temperature is 50-60°C.
4. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: The ratio of the added amount of precursor Mo2V2AlC3 powder to HF solution is (0.8~1.2)g:20mL.
5. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In S2, the reaction time is 72 to 144 hours.
6. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In S2, the washing process is: washing the centrifugally separated product with deionized water until the supernatant is neutral.
7. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In S2, the freeze-drying temperature is below -35°C and the time is 12 to 36 hours.
8. The method for preparing a high-performance magnesium-based composite hydrogen storage material according to claim 1, characterized in that: In S3, during the ball milling process, the ball-to-material ratio is controlled to be 55-65:1, the ball milling speed is 400-600 rpm, and the time is 8-12 hours.
9. A high-performance magnesium-based composite hydrogen storage material, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The composition of the composite hydrogen storage material is MgH2-x wt%Mo2V2C3.
10. Application of a high-performance magnesium-based composite hydrogen storage material as claimed in claim 9 in hydrogen energy vehicles and energy storage systems.
Citation Information
Patent Citations
Mg-Al-Y-based hydrogen storage material and preparation method thereof
CN113862536A